2006
DOI: 10.1073/pnas.0511253103
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ regulates glucose metabolism and insulin sensitivity

Abstract: The metabolic syndrome is a collection of obesity-related disorders. The peroxisome proliferator-activated receptors (PPARs) regulate transcription in response to fatty acids and, as such, are potential therapeutic targets for these diseases. We show that PPAR␦ (NR1C2) knockout mice are metabolically less active and glucoseintolerant, whereas receptor activation in db͞db mice improves insulin sensitivity. Euglycemic-hyperinsulinemic-clamp experiments further demonstrate that a PPAR␦-specific agonist suppresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
410
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(446 citation statements)
references
References 35 publications
24
410
3
2
Order By: Relevance
“…Further, a PathwayAssist analysis revealed that GK is closely linked to PPARα and SREBPs [2]. Recent studies have shown that G6PDH is a target gene for both PPARα, SREBP1c, and SREBP2 in liver [50,[57][58][59]. Together, these data indicate that it is likely that GK mediates the PPP through its network partners PPARα, SREBP1c, and SREBP2.…”
Section: Discussionmentioning
confidence: 86%
“…Further, a PathwayAssist analysis revealed that GK is closely linked to PPARα and SREBPs [2]. Recent studies have shown that G6PDH is a target gene for both PPARα, SREBP1c, and SREBP2 in liver [50,[57][58][59]. Together, these data indicate that it is likely that GK mediates the PPP through its network partners PPARα, SREBP1c, and SREBP2.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years PPARδ has emerged as a key protein in the regulation of energy metabolism by its ability to enhance fatty acid catabolism, energy uncoupling and insulin sensitivity in the liver, adipose tissue and skeletal muscle [6][7][8][9][10]36].…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, overexpression of Ppard in mice increases oxidative metabolism, changes muscle fibre type towards oxidative type I fibres and improves physical endurance thereby averting obesity induced by a high-fat diet or genetically [6,7]. Additionally, a recent study of genetically modified mice provides evidence that PPARδ regulates glucose metabolism and insulin sensitivity in both skeletal muscle and the liver, interestingly indicating a subtle PPARδ-controlled change in substrate utilisation [8]. Increased Ppard expression in adipose tissue in mice is associated with reduced adiposity and lower serum lipid levels [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The PPARα isoform, which is highly expressed in hepatocytes, controls fatty acid transport and β‐oxidation and dampens the inflammatory response 7, 8. The PPARδ isoform (also known as PPARβ) contributes to the regulation of glucose and lipid metabolism while exerting anti‐inflammatory properties in the liver by skewing M2 polarization of Küpffer cells 9, 10, 11. PPARγ and PPARδ are expressed at various levels in hepatic stellate cells (HSCs), a driver of liver fibrosis; PPARγ is key in keeping HSCs in a quiescent nonfibrogenic state 12, 13…”
Section: Introductionmentioning
confidence: 99%